Design and Evaluation of Mastectomy Bras Using 3D Virtual Prototyping - Gözde Ermin; Arzu Şen Kılıç (Applied Sciences, 2025)
This study aims to develop an innovative and functional mastectomy bra that addresses the physical, aesthetic, and psychological needs of post-mastectomy women. Mastectomy bras play a vital role in prosthesis stability, body image improvement, and quality of life. Using CLO 3D virtual fitting software-2024.2.214, two bra models were designed and evaluated for ergonomic fit and aesthetic appearance. The virtual prototyping method enabled design evaluation without physical sample production, providing an efficient and sensitive approach for user-centered design. Features such as prosthesis stability, user comfort, and aesthetic elements were optimized, while Tencel–PES–elastane and nylon–elastane fabrics were compared for pressure performance and body fit. Results showed similar performance for both fabrics; however, Tencel was recommended as a sustainable option due to its superior moisture absorption, breathability, and skin-friendly properties. The 3D virtual prototyping method offered an effective evaluation tool while addressing the psychological needs of women who prefer not to participate in physical fittings. This approach presents an innovative and sustainable model that can be applied to the design of other specialized garments. This study presents an innovative contribution by integrating advanced CLO 3D virtual prototyping technology into the design process, enabling ergonomic and aesthetic evaluations without the need for physical samples, especially for women in the sensitive post-operative period. This innovative approach not only streamlines the design process but also establishes a sustainable framework for specialized garment production. The utilization of Tencel–polyester–elastane fabric as a sustainable alternative demonstrates suitable performance in terms of comfort and ergonomic fit while promoting environmentally friendly practices. These findings highlight the significance of digital prototyping methods in garment design and offer a user-centric, eco-conscious model applicable to other specialized garments.